STRESS IN NURSING STUDENTS: AN INDONESIAN PILOT CASE STUDY - Imelda L Ritonga (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. Previous studies have found that severe stress can occur in nursing students because of their education system; however there have not been any studies to address stress in nursing students, conducted in Indonesian. The studies reinforce that stress in nursing students, is an important factor for nursing lecturers to consider in nursing education. Students felt helpless when they could not change situations they did not like and complained that the learning approach was authoritarian. This study identifi ed stressors in nursing students and effect of stress in the students’ learning process. Method. A case study was used with cognitive appraisal theory from Lazarus and Folkman (1984), as the theoretical proposition. Data was collected by utilizing in-depth interviews with nursing students. Results. There were fi ve evident themes found in this study related to stress and its effect on the students’ learning process. These Themes were: (1). Dormitory living, (2). Learning in the school, (3). Learning in the clinical setting, (4). Personal and socialbeliefs, and (5). Short-term and long-term effects. Discussion. Results indicated that education process used in this particular school of nursing, created stress which impacted adversely on the students’ learning process. Some of the problems identifi ed are specific to nursing education in Indonesian.Keywords: psychological stress, stressor, cognitive appraisal, coping